Yes-associated protein promotes endothelial-to-mesenchymal transition of endothelial cells in choroidal neovascularization fibrosis - Rong Zou; Yi-Fan Feng; Ya-Hui Xu; Min-Qian Shen; Xi Zhang; Yuan-Zhi Yuan (International Journal of Ophthalmology, 2022)
AIM: To reveal whether and how Yes-associated protein (YAP) promotes the occurrence of subretinal fibrosis in age-related macular degeneration (AMD). METHODS: Cobalt chloride (CoCl2) was used in primary human umbilical vein endothelial cells (HUVECs) to induce hypoxia in vitro. Eight-week-old male C57BL/6J mice weighing 19-25 g were used for a choroidal neovascularization (CNV) model induced by laser photocoagulation in vivo. Expression levels of YAP, phosphorylated YAP, mesenchymal markers [α smooth muscle actin (α-SMA), vimentin, and Snail], and endothelial cell markers (CD31 and zonula occludens 1) were measured by Western blotting, quantitative real-time PCR, and immunofluorescence microscopy. Small molecules YC-1 (Lificiguat, a specific inhibitor of hypoxia-inducible factor 1α), CA3 (CIL56, an inhibitor of YAP), and XMU-MP-1 (an inhibitor of Hippo kinase MST1/2, which activates YAP) were used to explore the underlying mechanism. RESULTS: CoCl2 increased expression of mesenchymal markers, decreased expression of endothelial cell markers, and enhanced the ability of primary HUVECs to proliferate and migrate. YC-1 suppressed hypoxia-induced endothelial-to-mesenchymal transition (EndMT). Moreover, hypoxia promoted total expression, inhibited phosphorylation, and enhanced the transcriptional activity of YAP. XMU-MP-1 enhanced hypoxia-induced EndMT, whereas CA3 elicited the opposite effect. Expression of YAP, α-SMA, and vimentin were upregulated in the laser-induced CNV model. However, silencing of YAP by vitreous injection of small interfering RNA targeting YAP could reverse these changes. CONCLUSION: The findings reveal a critical role of the hypoxia-inducible factor-1α (HIF-1α)/YAP signaling axis in EndMT and provide a new therapeutic target for treatment of subretinal fibrosis in AMD.